2003
DOI: 10.1385/bter:96:1-3:117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Supplementation on Oxidative Stress and Antioxidant Status in Iron-Deficiency Anemia

Abstract: This study was designed to measure the effect of iron supplementation on antioxidant status in iron-deficient anemia, including the time for hemoglobin normalization and at the time of filling of iron body stores. The extent of plasma lipid peroxidation was evaluated by measuring the levels of malondialdehyde and glutathione peroxidase (GSH-Px), and the activities of superoxide dismutase (SOD) and catalase in 63 patients with iron-deficiency anemia before and after 6 wk of iron supplementation and at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 13 publications
7
86
2
2
Order By: Relevance
“…Oxidant levels and antioxidant enzyme activities such as SOD, GSH-Px and CAT have been evaluated in several studies [8][9][10][11][12][13][14]. Although conflicting results have been reported [8,10], it is generally accepted that oxidative stress is increased through increase in oxidant levels and/or decrease in antioxidant enzyme capacities in IDA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Oxidant levels and antioxidant enzyme activities such as SOD, GSH-Px and CAT have been evaluated in several studies [8][9][10][11][12][13][14]. Although conflicting results have been reported [8,10], it is generally accepted that oxidative stress is increased through increase in oxidant levels and/or decrease in antioxidant enzyme capacities in IDA.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, decreased GSH-Px activity along with normal or increased SOD and CAT activity are the main findings in IDA [10,11]. However, in some studies, normal GSH-Px activity along with decreased SOD and CAT activity or decrease in all of these activities was also reported [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with our study, their study in patients with iron deficiency anemia also reported an increase in the levels of oxidant products, such as malondialdehyde and a decrease in the levels of the antioxidant enzymes, such as glutathione peroxidase. 16 In anemias, due to Thalassemia and G6PD enzyme deficiency, it has been shown that oxidative stress increases and antioxidant capacity is reduced. 17 In contrast, Acharya et al reported an increase in the levels of antioxidant enzymes in patients with iron deficiency anemia, and they suggested that this was due to overcompensation against the induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%